Belief in Luck and Precognition Around the World. (October 2022) - Harris, Emily A.; Milfont, Taciano L.; Hornsey, Matthew J.
Although magical beliefs (such as belief in luck and precognition) are presumably universal, the extent to which such beliefs are embraced likely varies across cultures. We assessed the effect of culture on luck and precognition beliefs in two large-scale multinational studies (Study 1: k = 16, N = 17, 664; Study 2: k = 25, N = 4, 024). Over and above the effects of demographic factors, culture was a significant predictor of luck and precognition beliefs in both studies. Indeed, when culture was added to demographic models, the variance accounted for in luck and precognition beliefs approximately doubled. Belief in luck and precognition was highest in Latvia and Russia (Study 1) and South Asia (Study 2), and lowest in Protestant Europe (Studies 1 and 2). Thus, beyond the effects of age, gender, education, and religiosity, culture is a significant factor in explaining variance in people's belief in luck and precognition. Follow-up analyses found a relatively consistent effect of socio-economic development, such that belief in luck and precognition were more prevalent in countries with lower scores on the Human Development Index. There was also some evidence that these beliefs were stronger in more collectivist cultures, but this effect was inconsistent. We discuss the possibility that there are culturally specific historical factors that contribute to relative openness to such beliefs in Russia, Latvia, and South Asia.